2020
DOI: 10.1002/dta.2810
|View full text |Cite
|
Sign up to set email alerts
|

The salmeterol anomaly and the need for a urine threshold

Abstract: Salmeterol is a long acting beta2-agonist (LABA) widely used for treatment of airways disease.There is evidence that beta2-agonists, including salmeterol, have the potential for performance enhancing effects when delivered at supratherapeutic doses. For this reason, all beta2-agonists are currently on the Prohibited List issued by the World Anti-Doping Agency (WADA) regardless of dosing route with some exemptions for inhaled salbutamol, formoterol, and salmeterol when used at therapeutic inhaled doses. For 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To strengthen the analysis, we also included data on urine concentrations of salmeterol and α‐hydroxysalmeterol from 37 biobank urine samples collected 1½–6 h after inhalation of 200 μg salmeterol in 13 endurance athletes (six with asthma and in current treatment with inhaled glucocorticoid, aged 23 ± 3 years and weighing 72 ± 8 kg), as well as 27 urine samples collected 4 h after inhalation of 100 μg salmeterol in 20 recreationally active men (10 with asthma, aged 25 ± 4 years and weighing 75 ± 6 kg) 22 . The salmeterol and α‐hydroxysalmeterol concentrations from the latter study were multiplied by 2 to approximate the maximum dosing limit of 200 μg, assuming dose linearity as observed during the pharmacokinetic trial (Figures 4 and 5) and apparent from between‐study analysis 41 . Thus, our prognostic analysis is based on 183 urine samples collected up to 6 h following inhalation of salmeterol in 44 individuals from three studies during controlled experimental conditions.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To strengthen the analysis, we also included data on urine concentrations of salmeterol and α‐hydroxysalmeterol from 37 biobank urine samples collected 1½–6 h after inhalation of 200 μg salmeterol in 13 endurance athletes (six with asthma and in current treatment with inhaled glucocorticoid, aged 23 ± 3 years and weighing 72 ± 8 kg), as well as 27 urine samples collected 4 h after inhalation of 100 μg salmeterol in 20 recreationally active men (10 with asthma, aged 25 ± 4 years and weighing 75 ± 6 kg) 22 . The salmeterol and α‐hydroxysalmeterol concentrations from the latter study were multiplied by 2 to approximate the maximum dosing limit of 200 μg, assuming dose linearity as observed during the pharmacokinetic trial (Figures 4 and 5) and apparent from between‐study analysis 41 . Thus, our prognostic analysis is based on 183 urine samples collected up to 6 h following inhalation of salmeterol in 44 individuals from three studies during controlled experimental conditions.…”
Section: Results and Analysismentioning
confidence: 99%
“…As recently highlighted by Jacobson and Hostrup, 41 the current salmeterol regulations are associated with some challenges that are potentially exploitable by athletes. The inclusion of α-hydroxysalmeterol in routine doping testing would provide superior prognostic accuracy to detect supratherapeutic use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These regulations include maximum permitted doses for formoterol, salbutamol, and salmeterol, 10 with corresponding urinary thresholds existing for formoterol and salbutamol, 133 while salmeterol is reported as AAF when exceeding 50% of the MRPL (i.e., 10 ng/ml). This strategy was called into question by Jacobson and Hostrup in the light of literature data regarding urinary levels of salmeterol following controlled therapeutic and supratherapeutic administrations as well as the aforementioned performance‐enhancing properties of the drug, and the authors suggest the installment of a threshold also for this β 2 ‐agonist 134 . More recently, tretoquinol was included as an example of banned β 2 ‐agonists in the Prohibited List, and Okano et al reported on the implementation of the drug and its main metabolites (tretoquinol glucuronide; tretoquinol sulfate; and free, glucurono‐, and sulfo‐conjugated O ‐methyl tretoquinol) into a routine ITP 135 .…”
Section: β2‐agonistsmentioning
confidence: 99%